1999
DOI: 10.1027//0269-8803.13.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Common Cold on Subjective Alertness, Reaction Time, and Eye Movements

Abstract: The present study examined whether volunteers with common colds showed impairments in objective and subjective indicators of alertness. All the volunteers (N = 81) were tested when healthy to provide baseline data for mood, simple and choice reaction time tasks, and an anti-saccadic eye movement task. When subjects developed a cold (N = 17) they returned to the laboratory and repeated the procedure. Volunteers (N = 64) who remained healthy over a 10-week period were recalled as controls. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…There are, however, examples where this approach has been used, and which may prove to be useful in the future. For example, Smith and colleagues (eg, [103][104][105]) have conducted a number of experimental studies of the effects of the common cold on cognitive performance using largely epidemiological recruitment methods. These are interesting approaches, especially as it has been argued that pain has interruptive effects on human cognitive performance [77,78], and so the common cold/influenza could be used to specifically investigate the effects of pain.…”
Section: Recruiting People With Urtimentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, examples where this approach has been used, and which may prove to be useful in the future. For example, Smith and colleagues (eg, [103][104][105]) have conducted a number of experimental studies of the effects of the common cold on cognitive performance using largely epidemiological recruitment methods. These are interesting approaches, especially as it has been argued that pain has interruptive effects on human cognitive performance [77,78], and so the common cold/influenza could be used to specifically investigate the effects of pain.…”
Section: Recruiting People With Urtimentioning
confidence: 99%
“…Recruitment in pain has been conducted [38] as have EMA techniques [56] Recruitment of participants when they report for pain treatment [124] Participants have been recruited at the point they seek treatment [82] Recruitment of those in pain is viable for menstrual pain Third molar extraction [73] Root canal treatment [96] and periodontitis [22] Recruitment of people when in pain [103][104][105] or seeking treatment is common [94] At risk Frequent recruitment of those at risk of pain [43,65,98] No studies were found recruiting those ''at risk'', however, risk factors are known [14,26] No evidence for at-risk recruitment those seeking analgesia following exercise, or following cosmetic procedures (eg, piercing, tattooing, depilation). Recruiting people whilst in pain provides both technical and ethical challenges, as it is not clear the extent to which people are able to consent to participation, especially if the study protocol requires temporarily withholding analgesia.…”
Section: Current Painmentioning
confidence: 99%
“…Hall and Smith (1996) found that having a cold was associated with a more negative mood and psychomotor impairment but little effect on other cognitive functions. These results were confirmed by Smith et al (1999a) in a study which also demonstrated that electrophysiological measures (speed of eye movements) are sensitive to the malaise associated with the common cold. Smith et al (1998) used virological assays to study the effects of the common cold on mood and performance.…”
Section: Naturally Occurring Urtismentioning
confidence: 54%
“…Indeed, an investigation of the effects of colds on speed of eye movements [19] has shown a similar slowing to that observed with sedative drugs. The reduction in arousal seen in those with a cold could be produced in several ways.…”
Section: Introductionmentioning
confidence: 67%
“…Studies of experimentally induced colds have shown that volunteers with colds have impaired psychomotor functioning (poor hand-eye co-ordination, slower response times in reaction time tasks [5,13,14]). Again, these findings have been replicated in studies of naturally occurring colds [15,16,17,18,19,20,21,22,23]. Some studies have used virological assays [20] to ensure that upper respiratory tract infections are being studied.…”
Section: Introductionmentioning
confidence: 89%